The effects and paths of regional industrial structure transformation on the fluctuation and quality of the marine fisheries economy in China - Wang, Bo; Li, Haiting; Sun, Pengyi; Zhang, Shaofeng; Zhang, Hongzhi (Frontiers in Marine Science, 2023)
Industrial structure adjustment is an important content of China's supply-side structural reform. From the perspective of advancement and rationalization, this paper studies the effect and action path of regional industrial structure on the economic fluctuation and quality of marine fishery, and draws several meaningful conclusions. There are differences in the impact of regional industrial structure on the economic fluctuation and quality of marine fisheries. First of all, the regional industrial structure advancement promotes the economic fluctuation of marine fishery. However, the rationalization reduces the economic fluctuation of marine fishery. Secondly, the influence path of regional industrial structure advancement on the economic quality of marine fishery presents a U-shape, while the influence path of regional industrial structure rationalization presents an inverted U-shape. At present, the industrial structure advancement index is higher than 5.029 in China's coastal areas, which is on the right side of the U-shape. This shows that promoting the regional industrial structure advancement evolution is conducive to improving the economic quality of marine fishery. The regional industrial structure rationalization level in Guangxi, Liaoning, Shandong, Guangdong, and Hebei is close to the optimal level (0.312), indicating that the industrial structure rationalization in these regions has a strong "structural dividend" for the economic quality of marine fisheries.